Severe acute inflammatory reaction (SAIR) of the fetlock joint after intraarticular hyaluronate injection in a horse - Kuemmerle, J. M.; Uhlig, H.; Kofler, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Hyaluronate (HA) was administered by intra-articular injection to a 13-year-old Haflinger mare for treatment of metacarpophalangeal osteoarthritis. Ten hours after the injection, a severe inflammatory reaction developed in the treated joint. While awaiting results of synovial fluid analysis, treatment for iatrogenic infectious arthritis was initiated, but the analysis did not confirm sepsis. Clinical signs improved significantly following systemic non-steroidal anti-inflammatory medication and the horse was discharged three days later. Following an intravenous hyaluronate injection, four days after discharge, the synovitis recurred. Synovial fluid analysis did not show any abnormalities, but the clinical signs were severe. The severe acute inflammatory reaction required systemic non-steroidal anti-inflammatory and intra-articular corticosteroid treatment in order to resolve the problem.
Keywords: Horse; SAIR; joint; arthritis; hyaluronate